Factors That Influence the Professional Success of the Selected Bsais Graduates at Bestlink College of the Philippines: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Professional success is defined as the sum of people's real and perceived positiveachievements as a result of their work experiences. However, there is no absolute measure ofachievement after completing the college level. Problems may occur in such situations, suchas finding job chances to put one's expertise to use.The researchers have found that the graduates prioritized their needs before wants andavoided financial obligations. They also enjoyed their workloads and strongly agreed thatemployees should be sent to training for development. In terms of career fulfillment, therespondents believed that their personality type, upbringing, and work-related values shapedtheir professional goals. Lastly, they rated positive mastery experiences as important fordeveloping their self-sufficiency. The researchers propose that BSAIS graduates should workon developing their financial literacy, time management skills, career planning, and self-confidence to become self-sufficient learners. Additionally, the researchers suggest that theBSAIS faculty should support the graduates in enhancing their financial literacy and engagethem in career planning to achieve their desired professional goals.In conclusion, this study provides valuable insights into the factors that influence theprofessional success of BSAIS graduates. The findings highlight the importance of financialliteracy, career planning, and self-sufficiency for achieving success in the accounting andinformation system field. The results of this study could be used by BSAIS graduates andfaculty to develop personal development plans and strategies that will help them achieve theirprofessional goals. Overall, this study contributes to the growing body of knowledge on thefactors that influence professional success and can be used to inform future research in thisarea.
Keywords: Business